Research progress on the preparation technology of molybdenum alloy piercing plug - PAN Yi-qing; TIAN Qing-chao; XU Wen-jin (Fenmo yejin jishu)
Molybdenum alloy piercing plug is one of the key tools in manufacturing the seamless tubular products using the high alloying steels such as stainless steels. The main influential factors affecting the mechanical properties and service life of the molybdenum alloy piercing plug were studied from the chemical composition, doping process, particle size, and sintering process. Firstly, the effects of alloying elements and adding method on the strengthening and toughening mechanism of the alloys were analyzed. Then, the influence of the powder doping processes and the particle size distribution and control on obtaining the compact homogeneous tissue in the subsequent preparation process was discussed. Finally, the advantages and disadvantages of the traditional sintering process, activated sintering technology, and new sintering technology were compared and analyzed, and some new ideas were provided for the future research of sintering forming technology.